The pacing differences in performance levels of marathon and half-marathon runners - Ristanovic, L.; Cuk, I.; Villiger, E.; Stojiljkovic, S.; Nikolaidis, P. T.; Weiss, K.; Knechtle, B. (Frontiers in Psychology, 2023)
Introduction Many studies indicate a considerable impact of optimal pacing on long-distance running performance. Given that the amount of carbohydrates in metabolic processes increases supralinearly with the running intensity, we may observe differences between the pacing strategies of two long-distance races and different performance levels of runners. Accordingly, the present study aimed to examine the differences in pacing strategies between marathon and half-marathon races regarding the performance levels of runners.